KEANEKARAGAMAN JENIS BURUNG DIURNAL DI KAWASAN HUTAN LINDUNG DESA TELUK BAYUR KECAMATAN SUNGAI LAUR KABUPATEN KETAPANG - Hasim, Abdul; Erianto, Erianto; Yani, Ahmad (Universitas Tanjungpura, 2021)
Protected forest is a forest area which has the main function of protecting life support systems. Currently, part of the Protected Forest Area of Teluk Bayur Village has turned into monoculture plantation land, so it is interesting to study. This study aims to obtain data on the diversity of diurnal bird species in the protected forest area of Teluk Bayur Village, Sungai Laur District, Ketapang Regency. The research was conducted using field observation techniques, direct observation with the path method (transect) combined with counting points. The research locations were divided into three locations based on land cover, namely primary, secondary and dominant oil palm forest cover. For each cover condition, 3 lines were made with each line made 6 count points. Based on the results of observations on three land cover conditions, it was found that 30 diurnal bird species were classified into 19 ethnic groups (families). Recorded 15 species of birds that are protected under CITES, IUCN and the Government Regulation of the Republic of Indonesia. The dominance index value (C) of diurnal birds in three cover conditions, namely between 0.0777 - 0.1373 is in the low category, which means that there are no speciesÂ dominant. The Species Diversity Index( ) in the three cover conditions, namely betweenÂ 2,1008 - 2,7220 is classified in the medium species diversity category. This is influenced by the carrying capacity of the environment, especially in forested areas. The evenness index value (e) in the three cover conditions, namely between 0.9245 - 0.9561, the value (e) is close to 1, which means that the distribution between species is relatively uniform. The species similarity index value on the three conditions of cover species similarity index (IS) value was <50%, which means that the observed species composition was not the same between the cover conditions.Â Keywords: Diurnal Birds, Species Diversity, Protected Forest.AbstrakHutan lindung adalah kawasan hutan yang mempunyai fungsi pokok sebagai perlindungan sistem penyangga kehidupan. Pada saat ini sebagian Kawasan Hutan Lindung Desa Teluk Bayur, telah berubah menjadi lahan perkebunan monokultur, sehingga menarik untuk dikaji. Penelitian ini bertujuan untuk mendapatkan data keanekaragaman jenis burung diurnal pada Kawasan Hutan Lindung Desa Teluk Bayur Kecamatan Sungai Laur Kabupaten Ketapang. Penelitian dilakukan dengan teknik observasi lapangan, pengamatan secara langsung dengan metode jalur (transect) dikombinasikan dengan titik hitung. Lokasi penelitian dibedakan atas tiga lokasi berdasarkan penutupan lahan, yaitu tutupan hutan primer, sekunder dan dominan kelapa sawit. Pada masing-masing kondisi tutupan dibuat 3 jalur dengan setiap jalur dibuat 6 titik hitung. Berdasarkan hasil pengamatan pada tiga kondisi tutupan lahan ditemukan sebanyak 30 jenis burung diurnal tergolong ke dalam 19 suku (famili). Tercatat 15 jenis burung yang dilindungi berdasarkan CITES, IUCN dan Peraturan Pemerintah Republik Indonesia. Nilai indeks dominansi (C) burung diurnal pada tiga kondisi tutupan yaitu antara 0,0777 - 0,1373 tergolong dalam kategori rendah, yang artinya tidak terdapat jenis yang mendominasi. Indeks Keanekaragaman Jenis ( ) pada tiga kondisi tutupan yaitu antara 2,1008 - 2,7220 tergolong dalam kategori keanekaragaman jenis sedang. Hal tersebut dipengaruhi oleh daya dukung lingkungan khususnya pada areal berhutan. Nilai indeks kemerataan jenis (e) pada tiga kondisi tutupan yaitu antara 0,9245 - 0,9561 nilai (e) mendekati 1 artinya distribusi antar spesies relatif seragam. Nilai indeks kesamaan jenis pada tiga kondisi tutupan nilai indeks kesamaan jenis (IS) <50%, dimana artinya bahwa antar kondisi tutupan yang diamati komposisi jenisnya tidak sama.Kata Kunci: Burung Diurnal, Hutan Lindung, Keanekaragaman Jenis.